Comparative in vitro study of two tooth bleaching systems: colour change and enamel surface effects - Grundlingh, Andries Adam (My University, 2010)
This in vitro study compares tooth bleaching and consequences of tooth surface effects of Ozicure Oxygen Activator (O3, RSA) with Opalescence Quick (Ultradent, USA) tooth bleaching. One hundred and thirty six teeth (canines, incisors and premolars), which were caries free, had no surface defects and within the colour range 1M2 and 5M3. Teeth were randomly divided into the three experimental groups: Opalescence Quick, Ozicure Oxygen Activator and control. The three experimental groups received three treatments of one hour each over three consecutive days. Tooth colour was assessed using the VITAPAN 3D MASTER TOOTH GUIDE (VITA, Germany) and VITA Easyshade (VITA, Germany). A randomized block design was used to assess tooth colour change. A General Linear Models test for analysis of variance for a fractional design with significance set at P<0.05 was used. Both bleaching methods significantly lightened the teeth, visually (P<0.0001) and digitally (P= 0.013). Tooth colour change was seen after the first hour of tooth bleaching; thereafter there was little or no benefit. The tooth type played a significant role in tooth colour change (visually P=0.0416 and digitally P=0.004). The quality of the spectrophotometer may account for the different results found compared to the tooth guide. Scanning electron microscopy showed no effect of enamel loss following bleaching. Atomic force microscopy showed a 2.5 rougher enamel surface with Opalescence Quick.
Thesis (M.Dent.), Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: colour change; tooth bleaching; enamel surface effects; visual tooth colour assessment; digital tooth colour assessment